ADVANTAGES OF USING ERP SYSTEM IN MANAGING RAW MATERIAL RESERVES: https://doi.org/10.5281/zenodo.15421200 - Imomyorov , Manusher (Journal of Contemporary World Studies, 2025)
This article examines the role and benefits of ERP (Enterprise Resource Planning) systems in improving the efficiency of enterprises in managing raw material reserves. Today, being competitive and using resources rationally is becoming increasingly important for enterprises. It was also noted that the ERP system increases the speed of decision-making and reduces human errors. Recommendations were developed to improve the effectiveness of the ERP system in inventory management.